LEVEL TEACHER SATISFACTION IN FOLLOWING CANVA APPLICATION TRAINING - Sylvia Persulessy; Mey Chyntia Yesaya; Hasan Bashri Hadimu (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
The use of appropriate media in learning is very necessary for teachers in the learning process. Teachers are required to use interesting and fun media so that learning objectives can be achieved. However, in the learning process, many problems arise between teachers who do not master technology. One thing that can be used to overcome this problem is to hold Canva application training for teachers. This research aims to determine the level of teacher enthusiasm in participating in training activities and their potential in developing digital-based teaching materials. This research uses a quantitative method with a survey approach by distributing questionnaires to teachers. The questionnaire was designed to measure the level of teacher satisfaction with training activities and their potential in developing digital-based teaching materials. To determine the achievements of this activity, data collection was carried out through two forms of instruments in the form of teacher peer assessment sheets and training participant satisfaction. The results of this research show that 79% of teachers who took part in the training were satisfied and greatly helped by the Canva application in learning. Each indicator that reflects the four forms of competence of the implementing team including pedagogical, professional, personality and social competence is considered successful in achieving the objectives of this training, namely so that teachers can utilize presentation media equipped with audio-visual content to convey lesson material to students. So that learning and teaching activities will become more varied and enjoyable. The findings of this research have important implications in the learning context at Maluku Advent High School. Apart from that, these findings also support the importance of training and professional development for teachers in adopting innovative learning technology